Online Credit Judgin From Sharia Economic Law - Marsela, Dina (MILRev: Metro Islamic Law Review, 2022)
The digital era or commonly known as 4.0 where everything is strived to shift to digitalization. One of the impacts of digitalization is in the fieldof muamalah (buying and selling transactions). Especially at this time in Indonesia experiencing a corona virus outbreak (Covid-19), where the government provides rules of life to the community so that activities are carried out at home as an effort to protect themselves. This activity will provide a surge in buying and selling transactions online, be it through Shoope, Tokopedia, Lazada, and others. Legal efforts are needed to identify whether the transaction is in accordance with the law in muamalah, namely fiqh muamalah? The method used in this research is legal research methods with qualitative analysis, the approach uses normative data. The result of the research is that online transactions are in accordance with muamalah fiqh, the use of the contract is the salam contract. This is because the community orders by giving the characteristics of the object of the item to be purchased, while the seller provides a description of the item itself in detail.